Primary progressive aphasia: a model for neurodegenerative disease. Issue 2 (April 2019) - Tee, Boon Lead; Gorno-Tempini, Maria Luisa
Abstract : Purpose of review: Knowledge on primary progressive aphasia (PPA) has expanded rapidly in the past few decades. Clinical characteristics, neuroimaging correlates, and neuropathological features of PPA are better delineated. This facilitates scientific studies on the disease pathophysiology and allows speech and language therapy to be more precisely targeted. This review article begins with a summary of the current understanding of PPA and discusses how PPA can serve as a model to promote scientific discovery in neurodegenerative diseases. Recent findings: Studies on the different variants of PPA have demonstrated the high compatibility between clinical presentations and neuroimaging features, and in turn, enhances the understanding of speech and language neuroanatomy. In addition to the traditional approach of lesion-based or voxel-based mapping, scientists have also adopted functional connectivity and network topology approaches that permits a more multidimensional understanding of neuroanatomy. As a result, pharmacological and cognitive therapeutic strategies can now be better targeted towards specific pathological/molecular and cognitive subtypes. Summary: Recent scientific advancement in PPA potentiates it to be an optimal model for studying brain network vulnerability, neurodevelopment influences and the effects of nonpharmacological intervention in neurodegenerative diseases.